Keeping Canada British : the Ku Klux Klan in 1920s Saskatchewan - Pitsula, James M. (James Michael), 1950- (UBC Press, 2013)
This provocative book provides a new interpretation of the Ku Klux Klan in 1920s Saskatchewan, arguing that it should not be portrayed merely as an irrational outburst of intolerance but as a slightly more extreme version of mainstream opinion that wanted to keep Canada British.